الفاعلية الأحيائية لبعـض المستخلصات النباتية والمركبات الصنعيّة على الأكاروس الأحمر ذي البقعتين Tetranychus urticae Koch ومفترسه Phytoseiulus persimilis Athias-Henriotمخبرياً - صقر, ابراهيم; مفلح, ماجدة; سليمان, رندة (Latakia University Journal -Biological Sciences Series, 2018)
Within the search for natural resources and chemical compounds that are more specialized , safer and less polluting for the environment , laboratory experiments were carried out to evaluate the bioefficacy of aqueous extracts , five plants Melia azedarach, Rosmarinus officinalis, Salvia officinalis, Smilax aspera and Styrax officinalis and three pesticides acetamiprid, abamectin and pyridabine on the eggs ,protonymph and the adults of both theTetranychus urticae and Phytoseiulus persimilis. Results showed a good effect of both the extracts of M.azedarach and S.officinalis where the mortality percentage exceeded 70 % on the protonymph and the adults and reached 57.33 % on the adults when they were treated with S.aspera.The mortality percentage was low with the extracts of both R. officinalis, S. officinalis,26.09% and 23.91% respectively, and reached 81.25 % on the adults when they were treated with pyridaben and72.92% with abamectin, while the effect was greater on the protonymph and it was less with the predator P. persimilis. Concerning the predator P. persimilis,it was found that the extract of the M.azedarach had the less effect32.61 % , therefore it was considered the best extract followed by the S.officinalis41.30 % on the adults. Abamectin recorded as the best pesticide was abamectin interms of its effect on the predator and T. urticae with mortality percentage reached 45.65 % and 72.92% respectively . The T. urticae hatchibility declined to 38 % when it was treated with M.azedarach extract and to 54 % with S.officinalis , 54% with abamectin and 4 % with pyridaben. The efficacy of the extracts and pesticides was low on the predator eggs, where the hatchability was 92 % with S.officinalis , 62% with M.azedarach and 90 % with abamectin, while there was no hatching with pyridaben نفذت تجارب مخبرية لتحديد الفاعلية الأحيائية لمستخلصات مائية لخمسة أنواع نباتية الأزدرختMelia azedarach، اكليل الجبل Rosmarinus officinalis، الميريمية Salvia officinalis، السمالكس Smilax asperaوالأصطرك Styrax officinalisوثلاثة مبيدات آكلوبرايد Acetamiprid، بيماكتين Abamectin وسانمايت Pyridabineعلى بيض وطور الحورية الأول وبالغات كل من الأكاروس الأحمر ذي البقعتين Tetranychus urticaeوالمفترس Phytoseiulus persimilis، ضمن إطار البحث عن مصادر طبيعية ومركبات كيميائية أكثر تخصصاً وأمانا ًوأقل تلويثاً للبيئة . أظهرت التجارب فاعلية جيدة لمستخلصي الأصطرك والأزدرخت على أفراد urticae. Tإذ تجاوزت نسبة القتل 70 % على الحوريات والبالغات، وصلت عند المعاملة بالسمالكس إلى 57.33%، جاءت نسبة القتل منخفضة مع مستخلصي كل من اكليل الجبل والميريمية 26.09 و23.91%على التوالي ووصلت إلى 81.25%عند المعاملة بالبيريدابين وإلى72.92%عند المعاملة بالأبامكتين على الأفراد البالغة، وكانت درجة التأثير أكبر على أفراد طور الحورية الأول. بالنسبة للمفترس P. persimilisوجد بأن مستخلص الأزدرخت امتلك التأثير الأقل %32.61 وبالتالي فهو المستخلص الأفضل تلاه الأصطرك S. officinalis41.30 %على الأفراد البالغة، أما فيما يتعلق بالمبيدات كان الأبامكتين الأفضل من حيث تأثيره على المفترس والأكاروس الضار وبنسبة قتل 45.65% و 72.92%على التوالي.انخفضت النسبة المئوية لفقس بيض urticae.Tإلى 38% لدى المعاملة بمستخلص الأزدرخت و54% لكل من الأصطرك والأبامكتين ووصلت إلى 4% مع البيريدابين. بدوره كان تأثير المستخلصات والمبيدات المختبرة منخفضاً على بيض المفترس، إذ بلغت نسبة الفقس 92% مع الأصطرك و62% مع الأزدرخت و90%مع الأبامكتين، باستثناء البيريدابين حيث لا يوجد أي فقس للبيض.